Life cycle externalities versus external costs: The case of inland freight transport in Belgium. (February 2019) - Merchan, Angel L.; Léonard, Angélique; Limbourg, Sabine; Mostert, Martine
Highlights: The Life Cycle Assessment of inland freight transport modes in Belgium for the year 2012 is conducted. Inland freight transport modes are assessed in terms of externalities and external costs. External costs are compared to externalities. The considered impacts are climate change, photochemical ozone formation and particulate matter formation. Externalities and average external costs cannot always be used interchangeably. Abstract: This paper proposes a case study on Belgium in which externalities and external costs of inland freight transport modes in Belgium are compared for the year 2012. The well-known Life Cycle Assessment methodology is used to identify the updated specific Belgian externalities related to three categories of negative impacts: climate change, photochemical ozone formation and particulate matter formation. The obtained values of externalities are then compared to the related external cost values. The objective is to determine if these two tools can be used interchangeably. We find that road transport has the maximum impact for every environmental impact indicator, with rail freight transport presenting the minimum one. We identify that each category of negative impact on the environment does not represent the same percentage of global externalities and external costs. In the analysis of the environmental impact per mode, it is observed that, when external costs are considered instead of externalities, the impact of road transport is slightly increased compared to both impacts of rail and inland waterways. Using externalities and average external costs interchangeably for estimating the impact of specific transport categories on the environment may thus lead to different results and different related policies.